Developing Physics Concept Understanding Skills: The Role of Interactive Media in Junior High Schools - Lubis, Maesaroh; Makwana, Darshil; Makwana, Gautam (Assyfa Learning Journal, 2025)
Understanding physics concepts is vital for junior high school students, yet many eighth graders struggle with measurement, heat effects, and temperature changes. This study evaluates the effectiveness of interactive media in enhancing physics understanding using the Borg and Gall model within a Research and Development (R&D) framework. Involving 50 students from a Bandung junior high school, the study employed educational software and interactive simulations over one semester. Data collection included in-depth interviews and pre- and post-intervention tests. Results indicated a 30% increase in average test scores, with 90% of students reporting heightened motivation and engagement. Tools like “Physics Explorer” and “Heat Dynamics” significantly improved active participation and conceptual grasp. The study advocates incorporating interactive media into physics curricula to enhance learning outcomes.